Reframing illegalities: crime, cultural values and ideas of success (in Argentina) - Moriconi, M. (Crime, Law and Social Change, 2018)
The expansion and entrenchment of insecurity, organized crime and violence in Latin America has involved the participation of public officials. Without this participation, it would be impossible to create the necessary niches of impunity to enable the growth of organized crime and violence. Using a hermeneutic-interpretative approach, this essay shows how the norm of legality has lost its moral persuasive power as a categorical imperative while certain illegalities have acquired social and political legitimacy. The purpose of this article is to reflect on the under-examined impact of cultural values on criminality. It also describes how the dominant narratives surrounding illegality and policies designed to reduce criminality are limited by a lack of consideration of the way that broader cultural values are permissive of corrupt and illegal behaviour. This article considers current social norms, interests, values, ideas of success, and the lack of legitimate pathways to achieve prosperity and social recognition to provide a fresh perspective on the discourse surrounding illegality. For the purpose of illustration this essay uses examples, evidence, interviews and discourses drawn from the context of Argentina. Far from being an anomaly, illegality is a fundamental part of both social inter-relations and has become institutionalised as a part of the behaviour of state entities. Illegality has become not only the norm but is seen as an effective and legitimate means to gain social success and prestige.